A study of Autonomic Dysfunction in bronchial asthma patients in a tertiary care centre of central India - Sudhir Mourya; Ratan Kumar; A Bajpai; D Jhaver; Shivani Mourya (International Journal of Medical Research and Review, 2014)
Introduction: bronchial asthma is a chronic inflammatory disorders of airways characterised by exaggerated bronchoconstriction due to certain indirect (e g dust, pollen, allergens, cold air) or direct (inhaled methacholine) stimuli. Autonomic system plays an important role in regulation of airways and their secretion. This study was planned to demonstrate existence of autonomic dysfunction in pathophysiology of bronchial asthma.Material & Methods: Present study is undertaken in 45 subjects who were divided in to 2 groups cases and controls depending up on age and sex and similar characteristics. 7 different non-invasive tests are applied in to all subjects to evaluate their autonomic function status.Results: It was found that out of 45 patients 33 patients had abnormal autonomic function tests. Comparing the duration of bronchial asthma, 12 patients had duration <5 years out of this 3 patients with duration of asthma <5 years had abnormal test the rest 9 had normal tests whereas 33 patients had bronchial asthma for >5 years out of these 30 had abnormal tests and only 3 patients had normal test. Comparing the severity of bronchial asthma and autonomic dysfunction, Out of 45 patients 24 were classified as having severe bronchial asthma. 21 of the study patients had only parasympathetic dysfunction i.e. 46.66%. 12 had both sympathetic and parasympathetic dysfunction i.e.40% and only 6 had isolated sympathetic dysfunction i.e. 13.33%.Conclusions: There is higher incidence of autonomic dysfunction in bronchial asthma patients. Parasympathetic hyper responsiveness appears to be the main pathological factor in the genesis of bronchial asthma